Measure The Benefits of Implementing a Business Intelligence System - Remigiusz TUNOWSKI (Communications of International Proceedings, 2022)
The study provides a theoretical description for a proposed research method to measure the benefits of implementing business intelligence systems. The potential benefit is defined here as a reduction in the time from the occurrence of a business event to decision-making by managers in the organization. As part of the search for a solution to the problem undertaken, the benefit of reducing time in the decision-making process is described, and delays in data processing and analysis are identified. A method for evaluating the impact of the Business Intelligence system on the decision-making process was also proposed. In addition, operational processes in organizations that can be evaluated first were identified. As a result, material was collected for a study on the impact of business intelligence systems on processes in organizations. An additional effect of this publication is that the research implications of a future study may suggest to decision-makers that the implementation of business intelligence systems can bring tangible benefits to organizations by indicating specific operational processes within the organization.
Keywords: Business Intelligence; Decision Making; Benefits Of Business Intelligence System